Book Review of "Nuclear Deviance: Stigma Politics and the Rules of the Nonproliferation Game" by Michal Smetana - Sannia Abdullah (International Journal of Nuclear Security, 2019)
In Nuclear Deviance, the author analyzes why some states are harshly treated by the nonproliferation regime, while others are granted exceptionalism in the existing nuclear order. Michal Smetana, with a new theory of nuclear deviance, describes a complex relationship of stigma politics with power and poses an interesting question for scholars to analyze if “deviance” is a neutral concept. In this scholarly contribution, the author explains that norm violation and deviance observed by state actors do not receive even treatment. “The inherently political character of stigma politics brings up the issue of double standards and divergent treatment of different actors in the nuclear order.” The premise of this argument is that nuclear order is based on fragile grounds, and “so are the categories of what constitutes a “normal” or “deviant” conduct in nuclear affairs” (p. 218). This book fills the gap on norms contestation by explaining the effect of norm violators in international politics.